Networked microgrids - Zhang, Peng (Cambridge : Cambridge University Press, 2021)
Discover scalable, dependable, and intelligent solutions to the challenges of integrating complex networked microgrids with this definitive guide to the development of cutting-edge power and data systems. Includes advanced fault management control and optimization to enable enhanced microgrid penetration without compromising reliability. Features SDN-based architectures and techniques to enable secure, reliable and fault-tolerant algorithms for resilient networked systems. Provides reachability techniques to facilitate a deeper understanding of microgrid resilience in areas with high penetration of renewables. Combining resilient control, fast programmable networking, reachability analysis, and cyber-physical security, this is essential reading for researchers, professional engineers, and graduate students interested in creating the next generation of data-intensive self-configurable networked microgrid systems, smart communities, and smart infrastructure.
Title from publisher's bibliographic system (viewed on 27 Apr 2021).
Keywords: Microgrids (Smart power grids).